Financial Feasibility of Layers Farming Business - Bakhtiar, Ary; Shodiq, Wahid Muhammad; Mazwan, M. Zul; Kombe, Luinasia Elikunda (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 17 No 3 (2023): Vol 17 No 3 (2023), 2024)
Egg prices exhibit high volatility over short time intervals, which is not surprising given their affordability and popularity as a primary protein source. However, this fluctuation in prices poses significant challenges for businesses, particularly in managing cash flow. Hence, it becomes crucial to evaluate the feasibility and sensitivity of the Layers farming business at PT JIF. The objective of this research is to provide a comprehensive analysis of the characteristics, financial aspects, cost flow, and overall feasibility of PT JIF's Layers farming operations. To achieve this, the study employs several data analysis methods, including the Net Present Value (NPV), Internal Rate of Return (IRR), Net B/C ratio, and Payback Period techniques. These methods are used to assess the economic viability of PT JIF's Layers farming business. The results demonstrate that PT JIF's layer farming business is indeed feasible, meeting the established investment feasibility criteria. Specifically, the NPV is greater than zero, the IRR exceeds the discount rate, the Net B/C ratio is higher than one, and the payback period is within three years, which is shorter than the commercial life of PT JIF's Layers farming business. For aspiring farmers venturing into the layer farming industry, it is advised to exercise patience, resilience, and consistency, considering the returnon-investment period of approximately three years. Moreover, future researchers are encouraged to conduct sensitivity analyses to explore the potential effects of uncertainties on PT JIF's Layers farming business in the long term. By incorporating such sensitivity analyses, a more comprehensive understanding of the business's potential performance under varying circumstances can be obtained. This, in turn, would aid in making informed decisions and implementing effective strategies for sustained success in the Layers farming sector